Ocena intensywności oraz efektów innowacji według działów przemysłu - Dąbrowski, Dariusz (Appraisal of Industrial Divisions According to Innovation Intensity and Performance, 2006)
This paper presents appraisal of Polish manufacturing divisions based on innovation intensity and share of sales of new and modernised products in total turnover. The appraisal has been performed with use of cluster analysis. Five clusters have been identified and relevant characteristics of them have been developed. In case of three clusters, an increase of innovation intensity was connected with increase of innovation performance. Two another clusters were outstanding, one with very high innovation effectiveness, and next one with low innovation effectiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 51-58